2021
DOI: 10.3390/cleantechnol3040042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Life Cycle Assessment of EPA and DHA Production from Microalgae and Farmed Fish

Abstract: The present study aims at comparing the life cycle environmental impacts of polyunsaturated fatty acids production (PUFA) from microalgae and farmed fish. PUFA production from microalgae cultivated via heterotrophy and photoautotrophy was assessed and compared. The primary energy demand (PED) and environmental impacts (EI) of PUFA production from microalgae via heterotrophy were significantly lower compared to PUFA produced via photoautotrophy. Furthermore, PED and EI of PUFA production from fish farmed in mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Since microalgal DHA + EPA is comparable with fish, replacing the fish oil with microalgal oil can be viable and sustainable [34]. This will thereby minimize the pressure of ocean fisheries and preserve the biodiversity [35]. Table 1 shows the fatty acid profile of some microalgal species.…”
Section: Current Sources Of Dhamentioning
confidence: 99%
“…Since microalgal DHA + EPA is comparable with fish, replacing the fish oil with microalgal oil can be viable and sustainable [34]. This will thereby minimize the pressure of ocean fisheries and preserve the biodiversity [35]. Table 1 shows the fatty acid profile of some microalgal species.…”
Section: Current Sources Of Dhamentioning
confidence: 99%
“…For a more techno-economical analysis on the same influencing factors, see Chauton et al ( 2015 ). From the environmental perspective, a focus on EPA produced from microalgae via heterotrophy is also desirable since studies have shown that the primary energy demand and environmental impacts of PUFA production from microalgae via heterotrophy were significantly lower compared to PUFA produced via photoautotrophy (Togarcheti and Padamati 2021 ) .…”
Section: Industrial Production and Market Valuementioning
confidence: 99%
“…Microalgal production of EPA and DHA was evaluated using heterotrophic or photoautotrophic conditions, and from farmed fish. 95 Algal pathways to these essential unsaturated fatty acids are needed, as the amount extracted from fish is not meeting the demand. Increase consumption of EPA and DHA may lead to overfishing, which results in habitat destruction and increased pressure on fisheries.…”
Section: Cultivation Harvesting and Processing Of Microalgaementioning
confidence: 99%